Effects of spatial plant–soil feedback heterogeneity on plant performance in monocultures. (8th January 2016) - Wubs, E. R. Jasper; Bezemer, T. Martijn
Summary: Plant–soil feedback (PSF) effects have almost exclusively been quantified on homogeneous soils, but as different plant species will influence their local soil differently, in reality PSF effects will be spatially heterogeneous. Whether plant performance in soils with spatially heterogeneous PSF can be predicted from pot experiments with homogeneous soils is unclear. In a glasshouse experiment, we tested the response of monocultures of six grassland species (two grasses, two legumes and two forbs) to three spatially explicit treatments (fine‐grained heterogeneity, coarse‐grained heterogeneity and homogeneous). Sixteen patches of conditioned soil (˜6 × 6 cm) were placed within each container. For homogeneous treatments, all patches contained the same conditioned soil within a container. The fine‐grained heterogeneous treatment contained four differently conditioned soils that were applied following a Latin square design, while for the coarse‐grained heterogeneous treatment, four contiguous square blocks of four cells each were created in each container. In general, species grew worse on soil conditioned by conspecifics. However, when the biomass production on all homogeneous soil treatments (own and foreign soils) was averaged and compared to the heterogeneous treatments, we found that biomass production was lower than expected in the heterogeneous soils. This effect of heterogeneity depended on both the conditioning and test species, but most heterogeneity effects were negative. The grain of the heterogeneity (coarse vs. fine: at the chosen spatial scale) did not affect plant performance. We hypothesize that a more diverse soil community is present in spatially heterogeneous soils. This increases (i) the chance of plants to encounter its antagonists, which may then rapidly increase in numbers; and (ii) the scope for synergistic co‐infections. Together, this may lead to non‐additive responses of plants to spatial heterogeneity in PSF. Synthesis . Plant performance was lower in spatially heterogeneous soils than predicted by spatially homogeneous soils. In natural grasslands that have mixed plant communities conditioning the soil, plant–soil feedback (PSF) effects on plant performance may therefore be more negative than what is predicted from pot experiments. Our results emphasize the need to incorporate the spatial dynamics of PSF both in empirical and modelling studies if we are to understand the role of PSF in plant–plant interactions and plant community dynamics. Abstract : We manipulated the spatial plant–soil feedback heterogeneity in soils and found that plant performance was generally lower in soils with spatially heterogeneous feedback than predicted by soils with homogeneous feedback. In natural grasslands that have mixed plant communities conditioning the soil plant–soil feedback, effects on plant performance may therefore be more negative than what is predicted from pot experiments.